Investigation on the Tree Species of Utlou Village, Bishnupur District, Manipur and their Uses - Laishram, Jogesh; Imotomba Singh, R.K. (Indian Forester, 2024)
The Utlou village of Bishnupur District, Manipur have great number of tree species. The current assessment was conducted in the Utlou village to evaluate the tree species found in this village and its uses by individuals living in the village. Thus a study was undertaken in the village and gathered information on trees and their uses. During the survey, household interview with the selected local elders were conducted to procure data on the uses of the tree species found nearby and furthermore to looked for their assistance in gathering the specimen of the tree species. The gathered tree specimen was then identified utilizing significant literary works. The scientific, common and local names and their uses were documented. The examination observed 81 tree species of 40 families and 72 genera which were utilized for 10 purposes in the study area. This investigation discovered that due to urbanization and development many trees were cut down and subsequently lost. Individuals living in the village to be encouraged for tree plantation and conserved the surrounding environment.